Pengaruh Dana Syirkah Temporer dan Islamic Corporate Governance Terhadap Kinerja Maqashid Syariah Bank Umum Syariah di Indonesia yang Terdaftar di Otoritas Jasa Keuangan (OJK) Periode 2017-2022 - Safitri, Razila Aulina; Mursidah, Mursidah; Indrayani, Indrayani; Yunina, Yunina (Jurnal Riset Mahasiswa Akuntansi, 2025)
This study aims to determine the influence of temporary syirkah funds and Islamic corporate governance on the performance of maqashid sharia of Sharia Commercial Banks in Indonesia registered in the Financial Services Authority for the period 2017-2022. This research uses secondary data in the form of annual reports from each Sharia Commercial Bank obtained from each Sharia Commercial Bank’s website. The sample in this study consists of 10 Sharia Commercial Banks in Indonesia registered with the Financial Services Authority for the period 2017-2022. The data analysis method used is multiple linear regression test using the help of Eviews version 10 software. The results of the study show that temporary syirkah funds and Islamic corporate governance partially do not significantly affect the performance of maqashid sharia. Meanwhile, based on the results of simultaneous tests, it was found that temporary syirkah funds and Islamic corporate governance simultaneously do not significantly affect the performance of maqashid sharia of Sharia Commercial Banks in Indonesia registered with the Financial Services Authority for the period 2017-2022. This indicates that both temporary syirkah funds and Islamic corporate governance do not have a significant impact or contribution in improving the performance of maqashid sharia of Sharia Commercial Banks in Indonesia.